Analysis of The Influence of Career Development and Training on Apparatus Performance in Magetan Regency - Utama, Lalu Satria; Kistyanto, Anang; Wardoyo, Dewie Tri Wijayati (Institut Agama Islam Sunan Giri Ponorogo, 2024)
This study aims to analyze the influence of career development and training on the performance of apparatus within the Magetan Regency Government, namely the Manpower Office, the Industry and Trade Office, the Cooperatives and SMEs Office, and the Social Service. This study uses a causal quantitative design. The sample was determined by a non-random sampling method, involving 65 respondents who were employees with functional and executive positions in the four Regional Government Organizations (ODP). Data analysis uses multiple linear regression. The analysis showed that career development and training positively and significantly affected the performance of apparatus or employees in the four OPDs within the Magetan Regency Government. This study shows that career development and training significantly affect apparatus performance within the Magetan Regency Government. It is recommended that qualitative research be conducted to explore more deeply the factors that affect career development and training effectiveness.